Fulminant myocarditis mimicking acute myocardial infarction in a 50 years old female patient with COVID19 proven infection. Issue 4 (December 2020) - Berkovitch, Anat; Wasserstrum, Yishay; Mayan, Haim; Vatury, Ori; Maor, Elad; Segev, Amit; Matetzky, Shlomi
No abstract available